2003
DOI: 10.1038/sj.ejcn.1601584
|View full text |Cite
|
Sign up to set email alerts
|

Social and dietary determinants of body mass index of adult Jamaicans of African origin

Abstract: Objectives: To determine the relationships between body mass index (BMI) and diet, social and behavioural factors among adult Jamaicans of African origin. Design: Cross-sectional. Setting: Urban communities in Jamaica, West Indies. Subjects: Three-hundred and sixty-three males and 561 females of African origin, aged 25 -74 y. Results: Women had higher mean BMIs (27.5 AE 6.4 kg=m 2 ) than men (23.4 AE 4.3 kg=m 2 ); 30.7% of women compared with 6.7% of men were obese. There was a tendency for obese men to have h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…The central tenet surrounding overweight and obesity is an imbalance where energy intake exceeds expenditure. Changes in dietary patterns in the past few decades, such as an increase in the consumption of energy-dense, high-fat and sugar-rich foods, and more sedentary lifestyles have been implicated in the pandemic of obesity (19,20,47) but the association between these dietary changes and the increase in obesity has not always been demonstrable in epidemiological studies (15) . Bivariate analysis showed that high consumption of fast foods (OR 5 1?84) and sweetened beverages (OR 5 1?52) was positively associated with overweight in both sexes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The central tenet surrounding overweight and obesity is an imbalance where energy intake exceeds expenditure. Changes in dietary patterns in the past few decades, such as an increase in the consumption of energy-dense, high-fat and sugar-rich foods, and more sedentary lifestyles have been implicated in the pandemic of obesity (19,20,47) but the association between these dietary changes and the increase in obesity has not always been demonstrable in epidemiological studies (15) . Bivariate analysis showed that high consumption of fast foods (OR 5 1?84) and sweetened beverages (OR 5 1?52) was positively associated with overweight in both sexes.…”
Section: Discussionmentioning
confidence: 99%
“…Among Jamaican adults, the prevalence of overweight and obesity increased from 26?5 % in 1995 (14) to 36?8 % in 2000 (15) . This is consistent with the ongoing epidemiological transition in middle-income countries.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] They found that St Catherine has a diverse population with congruent characteristics similar to the wider Jamaican population. The current study found that although a sample of older men in St Catherine had similar characteristics like a National sample (JSLC), some disparities still exist between the two samples.…”
Section: Accuracy Of National Surveys and Subsample Surveysmentioning
confidence: 99%
“…The sampling frame was men older than 55 years in the parish of St Catherine. The parish of St Catherine was chosen because previous data and surveys [11][12][13] suggested that it has the mix of demographic characteristics (urban, rural, and age composition) that typify Jamaica.…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation